An Analysis of Women’s Emancipation in the Novel Girl in Pieces in Obama’s Era - Imraini Imraini; Harianto II Harianto II; Dewi Nurmala (Fakultas Sastra UMN AL Washliyah, 2021)
This thesis contains an analysis of the emancipation of women in the novel entitled Girl in Pieces by Kathleen Glasgow. The method used in this research is qualitative method. The purpose of this study is to find out the type of female emancipation in the novel Girl in Pieces by Kathleen Glasgow in the Obama era in 2016 and to find out the impact of women's emancipation. Data is taken from the novel Girl in Pieces by Kathleen Glasgow. From results of the data analysis found that there are two types of emancipation found away the five types of emancipation, namely, the emancipation of women fostering progress / society. The positive impact of women's emancipation is that women can become independent and independent from men. And the negative impact of the emancipation of women is the absence of gender identity or the loss of gender identity during the Obama period.